2013
DOI: 10.1016/j.jaci.2012.10.060
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of milk allergy in an observational cohort

Abstract: Objective There are few studies on the natural history of milk allergy. Most are single-site and not longitudinal, and these have not identified a means for early prediction of outcomes. Methods Children aged 3 to 15 months were enrolled in an observational study with either (1) a convincing history of egg allergy, milk allergy, or both with a positive skin prick test (SPT) response to the trigger food and/or (2) moderate-to-severe atopic dermatitis (AD) and a positive SPT response to milk or egg. Children e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
251
4
17

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 339 publications
(278 citation statements)
references
References 26 publications
6
251
4
17
Order By: Relevance
“…Similar to our result, several studies found a relationship between atopic dermatitis and intolerance to cow's milk in CMA infants and children; however, moderate to severe type of atopic dermatitis was associated with a lower likelihood of developing tolerance (15,16). History of sensitization to certain foods such as egg has been reported with a worse prognosis in early life, but no significant association with intolerance to cow's milk was observed in this study (9).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar to our result, several studies found a relationship between atopic dermatitis and intolerance to cow's milk in CMA infants and children; however, moderate to severe type of atopic dermatitis was associated with a lower likelihood of developing tolerance (15,16). History of sensitization to certain foods such as egg has been reported with a worse prognosis in early life, but no significant association with intolerance to cow's milk was observed in this study (9).…”
Section: Discussionsupporting
confidence: 87%
“…In 9 European countries, 69% of children with CMA tolerated cow's milk one year after diagnosis, and all children with non IgE-mediated CMA and 57% of those with IgE-mediated CMA did so (14). A large cohort of 512 infants and children with CMA ranging from 3 to 15 months of age at 5 areas of the USA demonstrated a resolution rate of about 50% by age 5 (15). A natural course of CMA in 115 Korean children < 24 months of age with atopic dermatitis showed 50% tolerance at 67 months of age (16).…”
Section: Discussionmentioning
confidence: 99%
“…Выявлено влияние на прогноз развития толерант-ности к БКМ полиморфизма гена rs324015, ответствен-ного за выработку фактора транскрипции STAT6 и учаcтвующего в дифференциации Th2 [10].…”
Section: в практику педиатраunclassified
“…Напротив, заболевания с более поздним началом симптомов, кож-ными проявлениями, а также IgE-опосредованные фор-мы склонны к персистированию и требуют повторной оценки уровня специфических IgE в возрасте ~ 1 года [43]. В то же время тяжелые случаи аллергии к БКМ, как IgE-зависимые, так и не-IgE-зависимые, персисти-руют длительно, и дети могут никогда их не «перерасти» [10,43]. В целом, исследования показывают, что перси-стирующая аллергия к БКМ характеризуется значитель-но отягощенным семейным анамнезом по атопическим болезням, более длительным периодом между началом употребления БКМ и появлением первых симптомов аллергии, большей частотой множественных реакций на пищу и наличием других аллергических заболева-ний.…”
Section: заключениеunclassified
See 1 more Smart Citation